Explanatory theories of learning difficulties and their educational applications in the classroom - Djerdir, Fairouz (Journal of Human Sciences, 2020)
The field of learning difficulties is one of the most recent fields of special education that has attracted the attention of researchers, after their attention was focused on other fields in special education, such as mental and physical disabilities, but with the passage of time the field of learning difficulties has evolved in the school community and has received increasing attention, and has become a fertile field For researchers to present their theoretical perceptions, and the practical solutions that they see that would provide educational services for children with learning difficulties, as it has a role in helping teachers to adapt positively with this group in the classroom, and perhaps the most important contribution to achieving this goal is to know the most important theories Navel learning difficulties, and how to take advantage of educational applications when teaching this group of children to overcome these difficulties